Location of Cows and Pigs in Suburban Areas of Polish Metropolitan Centers - Benedykt Pepliński (Sustainability, 2020)
The main aim of this paper was to assess the impact of socioeconomic and agricultural factors on cow and pig density in suburban areas located up to 50 km from the 11 biggest cities in Poland. This study relied on data retrieved from all municipalities located within 50 km from central cities. The impact of the previously mentioned socioeconomic and agricultural factors was assessed using the Pearson correlation coefficient, analysis of variance (ANOVA), and regression analysis. This study shows that the lowest cow and pig density was recorded in the two inner rings. From 1996 to 2010, the gap between them and the levels recorded in other rings became much more pronounced. The analysis only corroborated the high correlation between livestock (cow and pig) density and the share of corresponding livestock farms in the total number of farms as well as the average herd size. Regarding other agricultural and socioeconomic factors, the correlation was weak or low except for a moderate correlation between the entrepreneurship indicator and pig density. The regression analysis demonstrated that the share of cow and pig farms in the total number of farms, average herd size, residential housing density, and unemployment rate had a significant impact on the density of animal groups considered.